A 10-year surveillance of antimicrobial susceptibility patterns in Shigella sonnei isolates circulating in Jiangsu Province, China. (September 2017) - Gu, Bing; Xu, Ting; Kang, Haiquan; Xu, Yanling; Liu, Genyan; Pan, Shiyang; Qian, Huimin; Ma, Ping
Highlights: Long-term multicentre surveillance of antimicrobial susceptibility patterns in Shigella sonnei . Epidemic clones and integron types and resistance gene cassettes were characterised. PFGE indicated large-scale clonal transmission among different cities occurred several times during 10 years. Class 1, 2 and atypical class 1 integrons were detected in S. sonnei . High prevalence of integrons and gene cassettes was related to the increasing antimicrobial resistance. Abstract: Objectives: The rapid emergence of drug-resistant Shigella sonnei is a serious public health problem. This study aimed to characterise the antimicrobial resistance patterns, molecular subtypes, and integron types and resistance gene cassettes in S. sonnei from Jiangsu Province, China. Methods: In total, 340 S. sonnei were collected in 2002–2011 throughout Jiangsu Province. Antimicrobial susceptibility testing, pulsed-field gel electrophoresis (PFGE), PCR amplification of integrons, restriction fragment length polymorphism (RFLP) and DNA sequencing of cassette regions were performed. Results: Resistance rates to ampicillin (67.7%), nalidixic acid (75.2%), tetracycline (73.7%) and trimethoprim/sulfamethoxazole (68.7%) remained high. Strains from Centre and South Jiangsu showed higher resistance and multiresistance rates compared with the North. PFGE analysis indicated that large-scale clonal transmission among different cities occurred several times during 10 years. Among all strains, 55.9% (190/340) harboured class 1 integrons, 80.3% (273/340) harboured class 2 integrons and 49.4% (168/340) harboured an atypical class 1 integron. Resistance rates to nine antimicrobials in the class 1 integron-positive group were significantly higher than in the negative group ( P < 0.05). Seven different gene cassettes were detected in class 1 integrons. The most prevalent type was aacA4 – cmlA1 (114/286). Class 2 integrons carried the gene cassette array dfrA1–sat1–aadA1, and the atypical class 1 integron carried bla OXA-30 – aadA1 . Conclusions: The increasing antimicrobial resistance and significant clonal transmission of S. sonnei circulating in Jiangsu were closely related to the high prevalence of integrons and gene cassettes. Long-term cross-regional monitoring of antimicrobial resistance is urgently required for S. sonnei .